Correction: Development and psychometric properties of Iranian midwives job satisfaction instrument (MJSI): A sequential exploratory study. - Ashraf Direkvand-Moghadam; Nasrin Rashan; Mona Bahmani; Safoura Taheri (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0262665.].